2010
DOI: 10.1017/s0033291709991899
|View full text |Cite
|
Sign up to set email alerts
|

The effect of referral for brief intervention for alcohol misuse on repetition of deliberate self-harm: an exploratory randomized controlled trial

Abstract: Referral for brief intervention for alcohol misuse following an episode of DSH may not influence the likelihood of repetition of self-harm. Longer-term interventions may be needed to help people who deliberately harm themselves and have evidence of concurrent alcohol misuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…31 Alcohol misuse is an important risk factor for deliberate self-harm. 32 Almost half of those presenting to services after an episode of deliberate self-harm have consumed alcohol in the period prior to the act. 32 Once again, earlier research has indicated that alcohol screenings were unacceptably low for this ED population 6 , yet there has been little change in the rate of alcohol screenings from 1993 to 2008.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Alcohol misuse is an important risk factor for deliberate self-harm. 32 Almost half of those presenting to services after an episode of deliberate self-harm have consumed alcohol in the period prior to the act. 32 Once again, earlier research has indicated that alcohol screenings were unacceptably low for this ED population 6 , yet there has been little change in the rate of alcohol screenings from 1993 to 2008.…”
Section: Discussionmentioning
confidence: 99%
“…32 Almost half of those presenting to services after an episode of deliberate self-harm have consumed alcohol in the period prior to the act. 32 Once again, earlier research has indicated that alcohol screenings were unacceptably low for this ED population 6 , yet there has been little change in the rate of alcohol screenings from 1993 to 2008. The conflicting evidence on the effectiveness of alcohol screenings and interventions in EDs, as well as the unreliability of self-reported alcohol use may be possible explanations for low screening rates.…”
Section: Discussionmentioning
confidence: 99%
“…Early feasibility trials suggested low rates of SBIRT service delivery among patients with a positive alcohol screen, with only 41 to 55% of such patients being offered an intervention (Hungerford, Pollock, & Todd, 2000; Peters, Brooker, McCabe, & Short, 1998). Fortunately, service delivery rates improved substantially in subsequent randomized clinical trials; nonetheless, approximately 11 to 30% of injured patients with a positive alcohol screen who consented to study participation were discharged before interventions could delivered (Blow et al, 2009; Crawford et al, 2010; Gentilello et al, 1999; Roudsari, Caetano, Frankowski, & Field, 2009). Moreover, a major trial evaluating SBIRT services in 14 academic emergency departments in the US revealed that 23.5% of patients with a positive alcohol screen were not enrolled in the trial because they were unable to provide consent or were excluded from the trial based on other clinical characteristics (Academic ED SBIRT Research Collaborative, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-three papers were included in the review [11-13,19-48]; see trial profile in Figure 1. The studies originated from United States (16), United Kingdom (6), Spain (3), Australia (2), Sweden (2), Denmark (1), Finland (1), Germany (1) and Switzerland (1).…”
Section: Resultsmentioning
confidence: 99%
“…Only one study [28] had a one-month follow-up visit and the adherence rate was 62%. The adherence rate after three months was 67% (54-96%) based on ten studies [19,20,22,27,28,35,36,39,40,48], after six months 72% (45-89%) based on 15 studies [11,23-25,27,29,30,33,36-38,41,44,47,48] and 67% (27-92%) after twelve months based on 15 studies [11,23-27,29,30,33,34,37,41,44-46]. …”
Section: Resultsmentioning
confidence: 99%